Ethnic identity & war : the Eurasians of Singapore during the Japanese Occupation - Anita Natasha Chand (2015)
The Eurasian community represents one of the oldest and most unique ethnic minorities in Singapore, who personify the legacies of the colonial period while embodying Asian sensibilities and culture. However, the ambiguity of their idiosyncratic identity of being neither fully European nor Asian has proven to be problematic in the history of their people. This research paper argues that the Japanese Occupation redefined the Singapore Eurasian community's public identity through reinforcing the British‟s refusal of inclusion of the Eurasians in the ranks of the Europeans in the colonial hierarchy, coercing the Eurasians to embrace their Asianness and utilise their idiosyncratic parentage as a means of survival, and sharing experiences that helped fostered a collective identity. Due to these factors brought about by the war, the community has come together collectively to accept the ambivalent state of their ethnic identity.